Эффективность комбинированной терапии деструктивных форм периодонтита (Эндодонтия Today)
Possibilities of the modern ultrasonic equipment promote deeper diffusion hydroxyapatite containing preparations in dentine tubules and lateral deltas of root channels of teeth, by results of scanning electronic microscopy. Measurement of density profile provides an objective estimation of features of regeneration of a bone fabric at stages of dynamic radiological control. In work the nearest and remote results of treatment of 93 patients with chronic apical periodontitis with which treatment by an advanced method of application of a preparation «Kollapan-gel K» in a combination to ultrasound and further by the analysis of density profile of roentgenograms the program «SIDEXIS XG» has been spent are considered.